High Density Lipoprotein Nanoparticles Deliver RNAi to Endothelial Cells to Inhibit Angiogenesis - Tripathy, Sushant (Particle & particle systems characterization : measurement and description of particle properties and behavior in powders and other disperse systems, 2014)
Systemic delivery of therapeutic nucleic acids to target cells and tissues outside of the liver remains a major challenge. We synthesized a biomimetic high density lipoprotein nanoparticle (HDL NP) for delivery of a cholesteryl modified therapeutic nucleic acid (RNAi) to vascular endothelial cells, a cell type naturally targeted by HDL. HDL NPs adsorb cholesteryl modified oligonucleotides and protect them from nuclease degradation. As proof of principle, we delivered RNAi targeting vascular endothelial growth factor receptor 2 (VEGFR2) to endothelial cells to effectively silence target mRNA and protein expression in vitro. In addition, data show that treatment strongly attenuated in vivo neovascularization measured using a standard angiogenesis assay and in hypervascular tumor allografts where a striking reduction in tumor growth was observed. For effective delivery, HDL NPs required the expression of the cell surface protein scavenger receptor type-B1 (SR-B1). No toxicity of HDL NPs was measured in vitro or after in vivo administration. Thus, by using a biomimetic approach to nucleic acid delivery, data demonstrate that systemically administered RNAi-HDL NPs target SR-B1 expressing endothelial cells to deliver functional anti-angiogenic RNAi as a potential treatment of cancer and other neo-vascular diseases